Educational impact on older adults’ well-being: a local case for general conclusion; Business Management Theories and Practices in a Dynamic Competitive Environment - Barysheva G. A. Galina Anzelmovna; Mikhalchuk A. A. Aleksandr Alexandrovich; Kareholt I. Ingemar; Casati F. Fabio; Nedospasova O. P. Olga Pavlovna; Terekhina L. I. Lyudmila Ivanovna (2020, 2020)
Title screen